How important is school environment in explaining individual variance of health behaviors? - Antonio Fernando Boing; SV Subramanian; Alexandra Crispim Boing (Universidade de São Paulo, 2019)
ABSTRACT We analyzed data from the National School-based Health Survey (PeNSE) carried out in Brazil in 2015 (n = 102,072 adolescents) to estimate how much of the individual variance in the prevalence of health behaviors is attributable to the school level. Multilevel logistic regression models were calculated to estimate the variance partitional coefficient (VPC) of the use of drugs, intake of unhealthy food, leisure physical activity and weight-related behaviors. The between-schools variance was significant in all tested models. The highest VPCs were observed when the use of drugs was analyzed (15%-20% of the total variance of smoking and use of illegal drugs). Lower, but still significant, values were observed in the other outcomes. The school context plays an important role in the adolescents' health and should be considered in the design of public policies and actions in public health.